Characteristics of blood pressure, arterial stiffness, and physical fitness in older adult Japanese community dwellers: a cross-sectional observational study - Masato Nishiwaki; Noriko Ogawa; Chika Nanayama; Naoyuki Matsumoto (Japanese Society of Physical Fitness and Sports Medicine, 2019)
The numbers of "old-old" and "young-old" adults (age ≥75 y [years] and 65-74 y, respectively) are now about the same, but less is known about the physiological characteristics such as arterial stiffness in old-old adults, especially those aged >85 y. Therefore, the present cross-sectional observational study aimed to determine the characteristics of blood pressure (BP), arterial stiffness, and physical fitness among 559 (male, n = 213; female, n = 346) Japanese community dwellers aged >65 y in Osaka and Kawakami Village, Nara. BP and arterial stiffness were measured in the supine position using a semi-automated device. Physical fitness was assessed by measuring handgrip strength and walking speed, as well as findings of the sit-and-reach and pegboard tests. Values for systolic BP, mean BP, and arterial stiffness were significantly higher in the old-old than young-old community dwellers. Trends in BP and arterial stiffness significantly increased, whereas those of physical fitness significantly decreased with age per decade. This is the first study to show that the physiological characteristics of BP, arterial stiffness, and physical fitness in Japanese community-dwelling older adults over 80 y. These novel findings indicate that community-dwelling older adults, especially nonagenarians, can maintain the longevity characteristics of lower arterial stiffness and higher physical fitness such as handgrip strength.